Pengaruh Layanan Informasi Teknik Modeling Simbolik Terhadap Self-Efficacy Pengambilan Keputusan Studi Lanjut - Wijayanti, Desy Nawangsari; Kurniawan, Kusnarto (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This research was held based on the phenomena that occured in SMP N 2 Ambalelections insecondary schoolsaffectedby theirfriendand was notsure of theplanningschoolof their choice. The lack of information makes the students confused in decision-making for further studies. The purpose of this research is to know the influence of symbolic modeling technique of information service toward self-efficacy decision-making for further studies. This research included in the experimentsresearch with one group pre test and post test design. The population of this research is the nine grade of SMP Negeri 2 Ambal. The sampling technique used was purposive sampling. Class IX E was being the sample with number of research respondents 30 students. The method of data collection in this study wasself-efficacy dalam Scale instrument decision-making for further studies. Methods of data analysis was descriptive percentage test and T-Test. Research results obtained, self-efficacy decision-making for further studies before symbolic modeling information engineering services given was 44.94% whereas after treatmentwas given it was being 82,36%. Thus, the symbolic modeling information engineering services can affect decision making self-efficacy for further studies.